Put on the Wig, It's Time to Ball - Allison Musser; Jon Welty Peachey (University of Kansas Libraries, 2016)
The purpose of this study is to explore the experiences of a collegiate men's basketball fan group. Little research has been undertaken exploring student fan groups, especially using ethnographic methods. The primary researcher attended two men's home basketball games at the University of Illinois at Urbana-Champaign, home of the student fan group, Orange Krush. The researcher also interviewed eleven Orange Krush members about their motivations and experiences in the group. The findings include a new benefit not previously found in the literature: Insider Access. An additional apparent theme was the importance of sport rituals, and the perception by the students that these rituals impact the outcome of the game. Finally, students indicated how the group improved their sense of community and diversity on campus. Implications of this research include sport management professionals emphasizing the importance of fan attendance on game success and ensuring fans feel they are closely connected to the teams so that they feel like insiders, which builds the emotional connection between fan and team.